Literasi Keuangan Syariah Generasi Z dan Minatnya pada Perbankan Syariah (Studi Kasus pada Siswa SMK di Jakarta) - Dian Sugiarti (Jurnal Ilmiah Ekonomi Islam, 2023)
Islamic financial literacy is one of the main factors in the development of Islamic banking. The low level of Islamic financial literacy, while Indonesia's Muslim population occupies the largest position in the world is a problem that needs attention. The potential for the development of the Islamic finance and banking industry can be carried out by increasing the Islamic financial literacy of the generation that dominates the population, Generation Z. This study looks at the effect of Islamic financial literacy on the interest in using Islamic banking in Generation Z. This study uses a quantitative approach with primary and secondary data. The research was conducted on students of class X, XI and XII Vocational High Schools in Jakarta. The samples taken in this study were 342 people. The data collection technique used the online questionnaire method for the respondents. The results of the study show that Islamic financial literacy has a positive and significant effect on Generation Z's interest in using Islamic banking products.